Problematika Sumberdaya Arkeologi Perkotaan: Studi Kasus Kota Lama Kendari - Sope, Amaluddin (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
This paper was written out of concerns about archaeological resources in the old town of Kendari which are currently under threat due to the rapid development. Here, factors causing this situation are identified and discussed. The data were collected through observation and library study, then analyzed to provide an overview of what actually occurred. Apparently, human factor played an important role in the loss of archaeological resources in Kendari, either due to ignorance, neglect or policy. This situation is exacerbated by obstacles in its preservation, namely the absence of a cultural heritage designation and the heritage expert team that is responsible for drafting heritage recommendation. This study suggests a number of conservation means to be carried out immediately: (a) establishing cultural heritage with its delineation limits, (b) formulating an area conservation policy through the RTRWK, (c) zoning, (d) involving the community, (e) socializing Cultural Conservation Law and its derivatives, and (f) the establishment of a participatory management body. === Tulisan ini berangkat dari keprihatinan terhadap sumberdaya arkeologi di kawasan kota lama Kendari yang saat ini terancam kelestariannya akibat pesatnya perkembangan kota. Sejumlah faktor penyebab keadaan itu terjadi diidentifikasikan dan didiskusikan. Pengumpulan data dilakukan melalui observasi dan penelusuran sumber pustaka. Hasilnya dianalisis dalam konteks yang lebih luas untuk dapat memberikan gambaran fenomena yang sesungguhnya terjadi. Rupanya, faktor manusia memainkan peran penting dalam musnahnya sumberdaya arkeologi di kawasan kota lama Kendari, baik karena ketidaktahuan, pengabaian, maupun kebijakan. Keadaan ini diperburuk dengan adanya hambatan dalam pelestariannya, yaitu belum adanya penetapan Cagar Budaya dan Tim Ahli Cagar Budaya. Kajian ini menyarankan sejumlah langkah pelestarian untuk segera dilakukan: (a) penetapan cagar budaya dengan batas delineasinya, (b) rumuskan kebijakan pelestarian kawasan melalui RTRWK, (c) melakukan zonasi, (d) pelibatan masyarakat, (e) sosialisasi UU No 11 tahun 2010 tentang Cagar Budaya dan turunannya, dan (f) pembentukan lembaga pengelola beranggotakan pemangku kepentingan.